Hymenoptera Parasitoid Diversity in Oil Palm Plantation on PT. Mopoli Raya, Aceh Tamiang, Indonesia - Aidil Amar; Husni Husni*; Abdullah Abdullah; Syaukani Syaukani (Universitas Syiah Kuala, 2021)
Hymenopteran parasitoids are biological control agents that contribute mortality to economically important pest of oil palm plantations. In this research we investigated the diversity and abundance of Hymenopteran parasitoids at PT. Mopoli Raya, Aceh Province, Indonesia. Data were collected by adopted a purposive sampling method in mature and immature plantations by using light trap, malaise trap, and yellow-pan trap. Specimens were identified at Universitas Syiah Kuala and final taxonomic confirmation was conducted at Gadjah Mada University. We found that the species richness and evenness of the Hymenoptera parasitoid species in mature oil palm plantations tended to be higher than in immature plantations. It is suspected that in immature oil palm plants (4 years) synthetic pesticide application is more intensive and it has a negative impact on the presence of parasitoids compared to the mature.